2018
DOI: 10.1589/jpts.30.1086
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic balance assessment using an unstable board in community-dwelling elderly people

Abstract: [Purpose] A new method for measuring dynamic balance was developed. The aim of this study was to describe the use of a novel “unstable board” to evaluate the balance ability of community-dwelling elderly individuals. [Participants and Methods] The following balance outcomes were evaluated in 59 community-dwelling elderly people: anteroposterior and mediolateral stability indexes on the unstable board, Mini-Balance Evaluation Systems Test score, the Functional Reach Test score, Timed Up-and-Go time, and the Fig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…Another recent publication describes the use of a new platform/unstable surface to assess the dynamic balancing capacity of people over 65 years of age living in the community. The average age of the participants is 70.5 + 3.5 years, and the average MMSE score is 28.6 points, taking into account that one of the exclusion criteria to participate in this study is an MMSE score <24 [33]. Other authors develop a new evaluation of the activities of daily living to determine the deterioration in daily functioning and ensure an early diagnosis of neurocognitive disorders in community-dwelling people over 65 years of age.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Another recent publication describes the use of a new platform/unstable surface to assess the dynamic balancing capacity of people over 65 years of age living in the community. The average age of the participants is 70.5 + 3.5 years, and the average MMSE score is 28.6 points, taking into account that one of the exclusion criteria to participate in this study is an MMSE score <24 [33]. Other authors develop a new evaluation of the activities of daily living to determine the deterioration in daily functioning and ensure an early diagnosis of neurocognitive disorders in community-dwelling people over 65 years of age.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The test was performed as the first assessment in the morning of the larger project's testing day to ensure mental or physical fatigue would not affect the results. [27][28][29][30] and individual Mini-BESTest total scores from an additional 137 healthy participants in four articles [31][32][33][34] These data were combined to form healthy control reference data groups for our analyses (see below). The available group-level data in the remaining 11 articles [35][36][37][38][39][40][41][42][43][44][45] were used for additional visual comparison.…”
Section: Mini-bestest Assessmentmentioning
confidence: 99%
“…Since we had no a priori criteria for how do deal with this situation, we included this participant in the analysis, but also repeated the analysis excluding the participant in order to examine if this individual score would have an effect on the overall results (this did not lead to any changes in the statistical significance outcomes of the tests, the direction of effects or the conclusions). Regarding the healthy control reference data, 327 healthy participants from eight articles [27][28][29][30][31][32][33][34] formed the control group for the Mini-BESTest total score and 190 healthy participants from four articles [27][28][29][30] formed the control group for the Mini-BESTest sub scores. Note that two of the contacted authors provided data for more participants than were reported in the identified study.…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…There are several tests that can be used to assess balance deficits, allowing early identification of elderly people with decreased balance capacity, to allow the implementation of interventions to prevent falls [4].…”
Section: Introductionmentioning
confidence: 99%